Ways of seeing : based on the BBC television series directed by Michael Dibb with the participation of John Berger. - Berger, John (London : British Broadcasting Corporation and Penguin Books, 2008)
"Ways of Seeing (Penguin Modern Classics) is a history, theory and criticism book written by John Berger. This book is based on a TV show on the BBC TV series with John Berger. This book was also made with the help of Richard Hollis, Michael Dibb, Chris Fox and Sven Blomberg. It explores an exclusive way of looking at art.A person's vision comes before their words, that is, a child may see and recognize something before they can learn how to speak and say it. It is vision that creates and helps people understand their surroundings in the world. It helps readers place themselves in the world. Some try to explain the world with words but they cannot undo the fact that they are surrounded by it. The association between people's vision for something and people's knowledge for something is never established.It consists of seven essays with images and words. The first four are said to have both words and images while the other three essays only have images. This book has helped contribute to the feminist readings in pop culture. It has essays that spotlight the portrayal of women in oil paintings and advertisements.Ways of Seeing (Penguin Modern Classics) by John Berger was published by Penguin UK in 2008. This book is available in paperback. Key Features: It can be used as a textbook for visual culture and art-history studies in university. This book has received positive review from critics."--
Keywords: Visual perception; Art -- Technique